2022
DOI: 10.2147/copd.s371765
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Red Blood Cell Distribution Width–Albumin Ratio and Hospital Mortality in Chronic Obstructive Pulmonary Disease Patients Admitted to the Intensive Care Unit: A Retrospective Study

Abstract: Purpose High levels of red blood cell distribution width (RDW) and hypoalbuminemia are markers of poor prognosis in chronic obstructive pulmonary disease (COPD) patients. However, few studies have shown that the red blood cell distribution width–albumin ratio (RAR) is related to the mortality of COPD. This study aimed to explore the relationship between RAR and hospital mortality in COPD patients admitted to the intensive care unit (ICU). Patients and Methods Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…High red blood cell distribution width (RDW) and hypoalbuminemia have also been shown to be associated with poor prognosis in COPD patients. 29 Among COPD patients admitted to the intensive care unit, higher RDW-albumin ratios were associated with short-term mortality. 29 In the present study, we confirmed that NPAR and NLR are both predictive of COPD mortality, and the performance of NPAR is slightly better than that of NLR.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…High red blood cell distribution width (RDW) and hypoalbuminemia have also been shown to be associated with poor prognosis in COPD patients. 29 Among COPD patients admitted to the intensive care unit, higher RDW-albumin ratios were associated with short-term mortality. 29 In the present study, we confirmed that NPAR and NLR are both predictive of COPD mortality, and the performance of NPAR is slightly better than that of NLR.…”
Section: Discussionmentioning
confidence: 98%
“…29 Among COPD patients admitted to the intensive care unit, higher RDW-albumin ratios were associated with short-term mortality. 29 In the present study, we confirmed that NPAR and NLR are both predictive of COPD mortality, and the performance of NPAR is slightly better than that of NLR. NPAR is a relatively new inflammatory marker, and few studies have explored its prognostic value.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…While RDW and albumin have been shown to be associated with an increased risk of atrial fibrillation [ 16 , 35 ], RAR, serving as a composite marker, exhibits a superior predictive effect. In recent years, it has been discovered that RAR is associated with type 2 diabetes and foot ulcers [ 36 ], chronic kidney disease [ 20 ], chronic obstructive pulmonary disease [ 21 ], acute myocardial infarction [ 22 ] and heart failure [ 37 ]. In AF, where inflammatory processes are known contributors, an elevated RDW/ALB ratio may signify a pro-inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…In mortality, the cut-off value of RAR is different in various research. In ICU, the cut-off RAR value was 5.51[30] for cancer, 5.315 for chronic obstructive pulmonary disease[34], 4.882 for septic patients with atrial fibrillation[35], 5.5 for sepsis[31], and 5.4 for aortic aneurysms[36]. And in non-ICU wards, the cut-off value was 3.809 for patients with diabetic foot ulcers[29].…”
Section: Discussionmentioning
confidence: 99%